Adequação dialítica em cães portadores de insuficiência renal crônica - Marina Thompson Santos Nunan (2008)
The objective of this study was to establish the most adequate dialysis for dogs suffering from chronic renal failure, considering the time of dialysis session, the interdialytic period and the low-flux dialyzers (high and low performance). There were four experimental groups of six animals each are: Group I: rats that underwent two hemodialysis sessions, with three hours each, interdialytic interval of 48 hours of dialysis and low performance. Group II: animals subjected to the two hemodialysis sessions, with three hours each, interdialytic interval of 48 hemodialysis and high performance. Group III: animals subjected to the two hemodialysis sessions, with three hours each, interdialytic interval of 72 hours of dialysis and low performance. Group IV: animals subjected to the two hemodialysis sessions, with three hours each, interdialytic interval of 72 hours of dialysis and high performance. Access was made through the external jugular vein, where a temporary catheter was implanted mono-lumen type "needle out," 14G gauge, polyurethane and length of 30.4 cm. To return blood was implanted in the cephalic venous catheter type temporary "needle through," Gage 20G of Vialon and length of 3.0 cm. To perform the dialysis were also used to share a single machine model 2008 C, a water treatment plant water WTU model 100 system with reverse osmosis and hemodialysis hollow fibers of the synthetic type of polysulfone. Anticoagulation was achieved with heparin at a dose of 100 IU / kg for priming, repeated the dose 25UI/Kg to 30 minutes, the last application made one hour before the end of dialysis. The mean blood flow was 120 ml / minute. Hematological evaluation revealed an increase in hemoglobin, packed cell volume, MCHC, WBC, segmented neutrophils and plasma proteins. In serum biochemistry showed a decrease in the values of concentrations of urea, creatinine, potassium, phosphorus and increase in the values of albumin and total protein, after dialysis. In assessing urinary changes were not observed under the dialysis procedure. The high performance dialyzers showed clearance about 20% more effective than the low performance for each dialysis session. The time of three hours of dialysis was able to debug, on average, 50% to 45% urea and creatinine. There was no significant difference between the interdialytic intervals of 48 and 72 hours.